The slow-fast dynamical behaviors of a hydro-turbine governing system under periodic excitations - Zhang, H.; Chen, D.; Xu, B.; Wu, Changzhi; Wang, X. (Spinger, 2016)
© 2016 Springer Science+Business Media DordrechtThis paper studies the dynamic evolution behaviors of the hydro-turbine governing system by using Adams–Bashforth–Moulton algorithm. Based on the non-autonomous dynamic model of the hydro-turbine governing system, the effects of the frequency and intensity of periodic excitation on the dynamic characteristics of the hydro-turbine governing system are analyzed in detail. Due to the different scales between the natural frequency and the excitation frequency, the fast-slow effect is obviously found on the behavior of the system under different motion modes. Furthermore, the influence rules of the fast-slow effect for the dynamic behavior of the hydro-turbine governing system are given. The results of the study can contribute to the optimization analysis and control of the hydro-turbine governing system in practical process.